The Threat of Green Grabbing to Indigenous Peoples’ Rights in the Implementation of Law Number 32 of 2024 - Mandala, Maulana Hendra; Muryani, Maria Ana; Rofiq, M.Khoirur (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to examine the threat of green grabbing in the implementation of Law No. 32 of 2024 concerning Natural Resource and Ecosystem Management, with a focus on its impact on land tenure by indigenous peoples and environmental governance. This study uses normative legal research methods by analyzing legislation, international legal instruments, and related academic literature. A doctrinal approach is applied to assess the alignment between the normative ideals of the law and the practical implications of Law No. 32 of 2024, particularly those related to the recognition of customary land rights and environmental management involving indigenous peoples. The novelty of this research lies in its critical assessment of the conservation framework as a potential instrument for land grabbing legalized by the state in the era after the enactment of Law Number 32 of 2024. This research highlights the tension between the goals of ecological preservation and the protection of indigenous peoples' rights, which are often neglected in the implementation of conservation policies. The results of the study show that although Law No. 32 of 2024 contains progressive principles such as community participation and recognition of indigenous peoples, its implementation remains weak. This is reflected in the lack of adequate recognition of customary land rights and the weak application of the Free, Prior, and Informed Consent (FPIC) procedure, which opens up opportunities for the misuse of conservation policies as a pretext for land grabbing. This study concludes that the effectiveness of Law No. 32 of 2024 depends on the establishment of clear technical regulations, strong protection mechanisms for customary territories, and integrative agrarian reform. To prevent conservation policies from becoming a justification for land grabbing, indigenous communities must be recognized not only as affected parties but as key stakeholders in natural resource management.